Utricularia julianae (Lentibulariaceae), a new species from the savannas of the Oyapock River, French Guiana - Delprete, Piero G. (Phytotaxa, 2014)
Utricularia julianae, a new species from the savannas near the Oyapock River, French Guiana, is here described and illustrated. The new species is most similar to U. tenuissima, from which it can be easily distinguished by the leaves and stolons apparently lacking (vs. leaves few and on the stolons, the stolons few or lacking, in U. tenuissima), traps ellipsoid, 0.3 mm long, with 4–5 capilliform appendages (vs. ovoid, 0.3–0.8 mm long, with 1 dorsal and 2 ventral slender appendages), corolla upper lip limb deeply bilobed (vs. broadly ovate to round), spur saccate, perpendicular to the lower lip (vs. spur narrowly cylindrical, parallel to the lower lip), among other characters. In addition, the capsules of U. julianae and U. tenuissima are unique within the genus, by being very narrowly ovoid, dehiscing by a single longitudinal slit, and with a placenta projecting outside the dehisced capsule. On the basis of their numerous morphological similarities and their peculiar capsule shape and dehiscence, the new species is tentatively placed within sect. Martinia, which P. Taylor described to accommodate U. tenuissima.